Clinical and instrumental evaluation of the efficacy a pulmonary artery banding with surgically treated congenitally corrected transposition of great arteries - Stohova, O.; Rudenko, N.; Khanenova, V.; Lebid, I.; Kuzmenko, Yu.; Prokhorovych, T. (Ukrainian Journal of Cardiovascular Surgery, 2017)
The pulmonary artery banding (PAB) is the one of the stages of surgery correction of CCTGA. Objectives: to evaluate the efficacy of the PAB as a stage of the surgery treatment in patients with CCTGA through the comprehensive echocardiography (echo) and angiography. Materials and methods. In a period from 2003 to 2017 in UCCC PAB was performed in 22 patients in age from 1 day to 7 years. Results and discussion.Indications for surgery banding pulmonary artery (PAB) in our experience were: the presence of non-restrictive ventricular septal defect (VSD), severe tricuspid insufficience, “training” of the morphological left ventricle (mLV) .The transesophageal echo carried out in the operation room for 4 patients. The pressure in the mLV during surgery, has averaged 52.3% from the systemic ventricle pressure. In the early postoperative period maximum gradient on PA by echo has averaged 47.9 mmHg. Intraoperative mortality was 4.5% (n=1). Two patients died in the late follow-up. The pressure in mLV before double switch operation according to angiography was 88.2% from pressure in mRV. The pressure gradient on PA was 70.1 mmHg by echo. The pressure gradient in patients before Glenn shunt on PA was 79.5 mmHg by echo. Conclusions. PAB in patients with CCTGA is recommended as a staged surgery . Intraoperative evaluation of the effectiveness PAB should be involve transesophageal echo. The determination of the optimal timing of staged surgical treatment of CCTGA after PAB is based on complex radiological methods of examination – echo and angiography.